INACTIVE, BUT NOT INEFFECTIVE: THE THERAPEUTIC POTENTIAL OF NON-REPLICATING BOVINE HERPESVIRUS TYPE-1 - Baracuhy, Enzo Mongiovi (My University, 2024)
Viral immunotherapy is a promising approach for cancer treatment where viruses can selectively target and kill cancer cells while also stimulating an immune response. Among viruses with this ability, Bovine herpesvirus type-1 (BHV-1) has several advantages, including previous data suggesting it does not require viral replication for its anti-cancer effects. We have previously demonstrated that binding and penetration of enveloped virus particles are sufficient to trigger intrinsic and innate immune signalling. In addition, we have published data showing mutated herpesviruses with lower replication in vitro exhibit stronger anti-tumour activity in vivo. Experiments in established animal models comparing the survival of mice bearing melanoma C10 cells treated with either live or UV (non-replicating) BHV-1 show that both viruses similarly extend survival. Transcriptomic analysis of C10 cells and tumours treated with either live or UV-inactivated BHV-1 has revealed a subset of overlapping differentially regulated genes and similar pathway enrichments, suggesting live and UV BHV-1 have similar mechanisms of activity. Lastly, the infiltration patterns of various immune cells in tumours following treatment with live and UV BHV-1 show that both viruses induce similar proportions of the same populations of immune cells, with the exception of neutrophils. This work highlights the potential of non-replicating BHV-1 as an effective immunotherapy and suggests that viral replication may not be necessary for therapeutic efficacy. These findings contribute to our understanding of the mechanisms underlying BHV-1 immunotherapy and provide insights into the immune response elicited by both live and UV-inactivated BHV-1, paving the way for further development of BHV-1-based cancer treatments.